Web-based information system for healthcare services - Gao, Chuping (2013)
Since the web based information technology grows very fast, and for now it becomes a highly developed technology and it is very convenient and effective for daily use and communication. So it will be ideal to use this technology to design and develop web based information system to provide healthcare services.